Establishment of Russian Oncology before the Great Patriotic War - S. Kh. Gantsev; V. V. Starinsky; A. M. Belyaev; O. N. Lipatov; K. Sh. Gantsev; S. R. Kzyrgalin; D. S. Tursumetov; Е. R. Ivanova; A. Kh. Gainullin (Креативная хирургия и онкология)
The establishment of oncology as a discipline in Russia should be considered taking into account the specifics of national history, as well as key historical events. In 2020, Russia celebrates the 75th anniversary of Victory in the Great Patriotic War (World Was II). Russian oncology also celebrates its 75th anniversary. April 30, 1945 is considered the birthday of the Russian oncological service connected with the publication of a historical resolution of the Council of People’s Commissars of the USSR No. 935 “On measures to improve oncological care to population.”In pre-revolutionary Russia, oncological care had the character of a private initiative, rather than a well-organised process. The tsarist government did not bear responsibility for organising the fight against cancer. The Great October Socialist Revolution contributed to the organisation of the fight against malignant neoplasms at the state level, based on the decisions of party congresses and healthcare laws. This created favourable conditions for improving and expanding anticancer care to the population. Soviet scientists-enthusiasts made a significant contribution to the development of oncology in the USSR. The organisation of medical professional societies facilitated the determination of main directions in the development of oncology as a discipline in the country. By the beginning of World War II, oncology in the USSR had acquired the character of an oncological care system, implementing measures aimed at developing and transferring into clinical practice early detection methods and those of treating malignant tumours, as well as their prevention. By the beginning of World War II, this system had comprised a large number of oncological dispensaries, located in almost all the republics of the Soviet Union. However, at that moment, there was still no unity in the creation of practical oncological institutions. Neither was practiced the registration of cancer cases, their account and observation, which measures are necessary for the prevention and early diagnosis of malignant tumours and precancerous diseases.